Critical factor in the application of diesel engines : a symposium arranged by the Combustion Engines Group and the Automobile Division of the Institution of Mechanical Engineers and the Diesel Engineers and Users Association, 22nd-24th September 1970 - Institution of Mechanical Engineers (Great Britain). Automobile Division (London : Institution of Mechanical Engineers, 1971)
20